فاعلية الأنساق الأنثوية في شعر فاطمة محمود سعد الله - خليف خضير الحياني, محمود; مهدي جابر العامري, رائدة (Journal of College of Education, 2021)
The first alphabets that were evident in the poem Candle in the Face of the Wind worked on a linguistic system that took from the path of sin that has been attached to the female throughout history as a way to bypass the pattern of male exclusion, as it was the demolition process that the poet initiated through the idea of ​​will, challenge, and freedom, which was embodied in The process of labor or birth from the womb of words, the brilliance and the manifestation, which took from the word a way to express the idea of ​​creation, organize and arrange things and reproduce them again in the poetic imagination through language, so that the dominant pattern changed was modified, modified, absorbed, and dissolved by means of Highlighting the ability of the woman (the female) to navigate the world of poetic words and the music of performances, as Al-Raheeih is the home of the new existence of the female, and its centralization, which began to fuse all the transcendents and the authority of the male pattern in an instant. New in which the real world is furnished, which can be undermined in the worlds of poetic imagination, which shows the effect of radiance and solemnity, which works to overcome the equation of nothingness into existence by the act of writing or the authority of the word on which the poetess focused.
Keywords: Dismantling, feminine, feminism, character, voice.